Maximizing indoor wireless coverage using UAVs equipped with directional antennas - Shakhatreh H.; Khreishah A.; Othman N.S.; Sawalmeh A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Base stations; Unmanned aerial vehicles (UAV); Cellular network; Data rates; Directional Antenna; Ground base stations; Multiple channels; Wireless base stations; Wireless coverage; Directive antennas